Nucleophosmin contains amyloidogenic regions that are able to form toxic aggregates under physiological conditions. Issue 9 (14th May 2015) - Di Natale, Concetta; Scognamiglio, Pasqualina Liana; Cascella, Roberta; Cecchi, Cristina; Russo, Anna; Leone, Marilisa; Penco, Amanda; Relini, Annalisa; Federici, Luca; Di Matteo, Adele; Chiti, Fabrizio; Vitagliano, Luigi; et al.
ABSTRACT: Nucleophosmin (NPM)‐1 is a multifunctional protein involved in a variety of biologic processes and has been implicated in the pathogenesis of several human malignancies. To gain insight into the role of isolated fragments in NPM1 activities, we dissected the C‐terminal domain (CTD) into its helical fragments. In this study, we observed the unexpected structural behavior of the peptide fragment corresponding to helix (H) 2 (residues 264‐277). This peptide has a strong tendency to form amyloidlike assemblies endowed with fibrillar morphology and β‐sheet structure, under physiologic conditions, as shown by circular dichroism, thioflavin T, and Congo red binding assays; dynamic light scattering; and atomic force microscopy. The aggregates are also toxic to neuroblastoma cells, as determined using 3‐(4;5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide reduction and Ca 2+ influx assays. We also found that the extension of the H2 sequence beyond its N terminus, comprising the connecting loop with H1, delayed aggregation and its associated cytotoxicity, suggesting that contiguous regions of H2 have a protective role in preventing aggregation. Our findings and those in the literature suggest that the helical structures present in the CTD are important in preventing harmful aggregation. These findings could elucidate the pathogenesis of acute myeloid leukemia (AML) caused by NPM1 mutants. Because the CTD is not properly folded in these mutants, we hypothesize that the aggregation propensity of this NPM1 region is involved in the pathogenesis of AML. Preliminary assays on NPM1‐Cter‐MutA, the most frequent AML‐CTD mutation, revealed its significant propensity for aggregation. Thus, the aggregation phenomena should be seriously considered in studies aimed at unveiling the molecular mechanisms of this pathology.—Di Natale, C., Scognamiglio, P. L., Cascella, R., Cecchi, C., Russo, A., Leone, M., Penco, A., Relini, A., Federici, L., Di Matteo, A., Chiti, F., Vitagliano, L., Marasco, D. Nucleophosmin contains amyloidogenic regions that are able to form toxic aggregates under physiological conditions. FASEB J. 29, 3689‐3701 (2015). www.fasebj.org